Transgenic Tall Fescue and Maize with Resistance to ALS-Inhibiting Herbicides - Sato, Hiroko; Takamizo, Tadashi; Horita, Junko; Kawai, Kiyoshi; Kaku, Koichiro; Shimizu, Tsutomu (IntechOpen, 2011)
None